Preparation method of multifunctional cardiovascular coating material with super-hydrophilicity
By using amphoteric ionized dendritic macromolecules and optimized coating preparation processes, the problems of insufficient hydrophilicity, weak bonding force, and limited functionality in cardiovascular coating materials have been solved. This has enabled the stability and biocompatibility of multifunctional cardiovascular coatings, making them suitable for complex device surface modification and providing safe and effective treatment options.
Patent Information
- Application Number
- CN202511714367.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-11-21
- Publication Date
- 2025-12-19
AI Technical Summary
Existing cardiovascular coating materials have shortcomings such as short hydrophilicity retention time, insufficient adhesion to the substrate, single function, and complex preparation process, making it difficult to achieve a balance between multiple biological requirements such as anticoagulation, antiproliferation, antibacterial and endothelialization promotion.
By employing amphoteric ionized dendritic macromolecules and an optimized coating preparation process, a stable multifunctional cardiovascular coating is formed through rigorous surface pretreatment, ultraviolet cross-linking, and low-temperature plasma sterilization. This coating is then further functionalized using heparin sodium solution to achieve superhydrophilicity, anticoagulation, and endothelial cell selectivity.
It significantly improves the stability and biocompatibility of the coating, reduces the risk of thrombosis, enhances the promotion of endothelial cells, and also has antibacterial and antiproliferative capabilities, adapting to the surface modification needs of complex instruments and ensuring the consistency of product quality.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of biomedical materials, and particularly relates to a preparation method of a multifunctional cardiovascular coating material with superhydrophilicity. BACKGROUND
[0002] Cardiovascular diseases have become one of the main causes of human death and disability worldwide. With the rapid development of interventional medical technology, cardiovascular implant devices such as vascular stents and interventional catheters play an irreplaceable role in clinical treatment. However, after being implanted into the human body, the surface of these devices will contact with blood components, which will trigger a series of complex biological reactions, including non-specific protein adsorption, platelet activation and adhesion, thrombosis, intimal hyperplasia, and infection complications. These problems seriously restrict the long-term efficacy and safety of the devices. To improve the biocompatibility of the devices, surface coating technology has emerged as the research focus in this field. Early coating materials mainly rely on heparinized coating or phospholipid polymer coating, which can improve the blood compatibility to some extent, but still have many limitations, such as the risk of thrombocytopenia induced by heparin, and the instability of traditional polymer coatings in complex blood flow environment. In addition, single-function coatings cannot meet the multiple challenges in clinical applications. How to balance the multiple goals of anticoagulation, anti-proliferation, antibiosis, and endothelialization is still a key problem that the existing technology has not solved well.
[0003] The cardiovascular coating technology in the current market mainly faces the following challenges: first, the hydrophilicity of the coating is short-lived and can easily decay under the action of body fluid flushing and mechanical stress, leading to an increased risk of thrombosis in the later stage; second, the bonding force between the traditional coating and the substrate is limited, which may cause peeling off and lead to serious complications such as vascular embolism; third, most coating designs are single-function, which cannot simultaneously meet the multiple biological requirements of anti-protein adsorption, anti-platelet adhesion, inhibition of smooth muscle cell proliferation, and promotion of endothelial cell repair; fourth, the existing coating preparation process is complex, especially for tubular instruments with complex geometrical shapes, it is difficult to achieve uniform and stable coating coverage. In recent years, superhydrophilic coatings based on zwitterionic polymers have shown unique advantages. They effectively resist non-specific protein adsorption by constructing a tight hydration layer, but there is still room for improvement in molecular structure design, accurate control of functional groups, and long-term stability. At the same time, how to combine biomimetic structure with multifunctional integration to develop intelligent coatings with excellent mechanical properties and specific biological functions has become an important development direction in this field.
[0004] With the progress of material science and surface engineering technology, the design concept of new generation of cardiovascular coating materials is undergoing profound changes. Researchers begin to design coating structure from the molecular level, and regulate the interaction between materials and biological environment by simulating the surface characteristics of biological membranes. Super-hydrophilic surface can significantly reduce protein and cell adhesion by forming a firm hydration layer, and zwitterionic materials are widely concerned due to their excellent anti-fouling performance. However, the existing technology uses biomaterials such as polypeptides, proteins and the like to construct biomimetic coatings, which has problems of poor batch stability and high cost; and the chemically synthesized coating often faces the challenges of single function and insufficient biological activity. Therefore, developing a cardiovascular coating material based on a fully chemical synthesis route, with a clear molecular structure, adjustable surface characteristics and integrated multiple biological functions, not only has important scientific significance, but also will provide a safer and more effective treatment plan for the clinic. The present application is in this context, by innovatively designing zwitterionic dendrimer modified compounds, combined with optimized coating preparation process, aims to break through the bottleneck of the existing technology, and provide a surface modification solution with excellent comprehensive performance for cardiovascular implant devices. SUMMARY
[0005] In view of the shortcomings of the prior art, the purpose of the present application is to provide a preparation method of a multifunctional cardiovascular coating material with super-hydrophilicity.
[0006] In the first aspect of the present application, a preparation method of a multifunctional cardiovascular coating material with super-hydrophilicity is provided, comprising the following steps:
[0007] S1, sequentially immerse the vascular stent in acetone, ethanol and deionized water and ultrasonically clean; immerse the cleaned device in a mixture of concentrated sulfuric acid and hydrogen peroxide solution, and treat at 58-62 DEG C to obtain a heat-treated vascular stent; transfer the heat-treated vascular stent into a toluene solution of 3-aminopropyl triethoxysilane, and react at 64-66 DEG C under nitrogen protection; finally rinse with deionized water, dry with nitrogen, and obtain an aminated vascular stent surface;
[0008] S2, dissolve hydroxyethyl methacrylate, acrylamide and zwitterionic polypeptide dendrimer in a phosphate buffer solution with pH 7.2-7.6 to form a solution, add genipin, polyethylene glycol-poly lactic acid block copolymer and 2-hydroxy-2-methyl propiophenone, and stir under light shielding conditions to obtain a coating solution; coat the coating solution on the aminated vascular stent surface to obtain a coated vascular stent;
[0009] S3, place the coated vascular stent in an ultraviolet crosslinking instrument under nitrogen protection, and irradiate under ultraviolet light; transfer to a constant temperature and humidity box and keep at 24-26 DEG C; then immerse in physiological saline at 36-38 DEG C to obtain a crosslinked vascular stent coating.
[0010] S4, the crosslinked vascular stent coating is immersed in a heparin sodium solution, soaked at 2-6 DEG C, to obtain a functionalized coating; the functionalized coating is washed with sterile deionized water, dried in a vacuum drying oven, and finally sterilized by low temperature plasma.
[0011] In the application, the preparation process of the cardiovascular coating material includes four key stages: the vascular stent is first subjected to strict surface pretreatment, ultrasonic cleaning with acetone, ethanol and deionized water in sequence, surface activation treatment with a mixed solution of concentrated sulfuric acid and hydrogen peroxide at a specific temperature, amino modification in a toluene solution in an inert atmosphere by using a silanization reagent to form a reactive instrument surface; then hydroxyethyl methacrylate, acrylamide and the aforementioned synthesized zwitterionic dendrimer are dissolved in a phosphate buffer solution, a genipin crosslinking agent, a polyethylene glycol-poly lactic acid block copolymer porogen and a photoinitiator are added, a uniform coating solution is formed under light shielding conditions, and the solution is coated on the surface of the pretreated stent; then ultraviolet-induced crosslinking is carried out under nitrogen protection, a porous structure is constructed through a phase separation process, and a stable three-dimensional network coating is formed after removing the residual porogen through physiological saline treatment; finally, secondary functionalization is carried out through a heparin sodium solution at low temperature, the coating is washed with sterile water and dried in a vacuum, and low temperature plasma sterilization treatment is carried out to obtain a multifunctional cardiovascular coating with superhydrophilicity, anticoagulant property and endothelial cell selectivity.
[0012] According to the preferred embodiment of the application, in step S1, the treatment time at 58-62 DEG C is 30-60 min.
[0013] According to the preferred embodiment of the application, in step S2, the stirring time under light shielding conditions is 4-6 h.
[0014] According to the preferred embodiment of the application, in step S3, the condition at 24-26 DEG C is maintained for 12-14 h.
[0015] According to the preferred embodiment of the application, in step S4, the soaking time at 2-6 DEG C is 24-30 h.
[0016] According to the preferred embodiment of the application, the preparation steps of the zwitterionic polypeptide dendrimer include:
[0017] A1, dissolve the fourth generation polyamidoamine dendrimer in anhydrous dimethyl sulfoxide, add bromoacetic acid and N,N'-diisopropyl carbodiimide, and react at 24-26 °C under nitrogen protection; then distill under reduced pressure to obtain a solid product, re-dissolve the solid product in a boric acid buffer solution with pH = 8.4-8.6, add ethylenediamine, and react at 3-5 °C to obtain an activated dendrimer, which is purified by dialysis;
[0018] A2, dissolve 2-methyl-2-oxazoline and 2-ethyl-2-oxazoline in acetonitrile, add methyl p-toluenesulfonate, and reflux at 78-82 °C under nitrogen protection to obtain a linear polyoxazoline intermediate; cool to 40-50 °C, add a sodium methoxide solution in methanol, and react at 60-65 °C; then add 2-acrylamide-2-methylpropanesulfonic acid, 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride, and N-hydroxysuccinimide, and react at 25-30 °C; finally, purify by precipitation with cold ethanol to obtain a sulfonic acid group functionalized polyoxazoline side chain;
[0019] A3, dissolve the activated dendrimer prepared in step A1 in a 2-morpholinoethanesulfonic acid buffer solution with pH 6.4-6.6, add the sulfonic acid group functionalized polyoxazoline side chain prepared in step A2, and react at 3-5 °C, and then continue to react at 24-26 °C; after the reaction is completed, purify by ultrafiltration to obtain a dendrimer-polyoxazoline conjugate; dissolve the dendrimer-polyoxazoline conjugate in a carbonate buffer solution with pH = 8.8-9.2, add dimethylaminoethyl methacrylate and azobisisobutyronitrile, and react at 70-75 °C to introduce a tertiary amine group; then sequentially add 1,3-propanesultone and iodomethane, and stir at 44-46 °C to form a zwitterionic structure;
[0020] A4, dissolve the zwitterionized dendrimer-polyoxazoline conjugate prepared in step A3 and dopamine hydrochloride in a sodium acetate buffer solution with pH 4.8-5.2, add N-(3-dimethylaminopropyl)-N'-ethyl carbodiimide hydrochloride and N-hydroxysuccinimide, and react at 24-26 °C under light shielding and nitrogen protection to obtain a reaction mixture; purify the reaction mixture by size exclusion chromatography and ion exchange chromatography, and finally freeze-dry.
[0021] In the application, the preparation process of the zwitterionic polypeptide dendrimer comprises four continuous steps: firstly, a fourth generation polyamide-amine dendrimer is used as a skeleton, reacted with bromoacetic acid and N,N'-diisopropyl carbodiimide in anhydrous dimethyl sulfoxide, and then reacted with ethylenediamine in a boric acid buffer system to realize functional group conversion, so as to obtain an activated dendrimer; secondly, an oxazoline monomer is subjected to ring-opening polymerization in an acetonitrile system, and an amine is subjected to a catalysis of sodium methoxide to realize an amine cleavage reaction, so as to condense a polyoxazoline intermediate and an acrylamide derivative containing a sulfonic acid group, and to construct a side chain structure with sulfonic acid functionalization; thirdly, the two intermediates are coupled in a buffer through a multi-step coupling reaction to assemble a dendrimer-polyoxazoline conjugate, and then the conjugate is subjected to radical grafting with dimethylaminoethyl methacrylate and azobisisobutyronitrile, and then subjected to sulfonation with propenesulfonic acid lactone and quaternization with iodomethane, so as to finally form a zwitterionic structure with both sulfonic acid groups and quaternary ammonium groups; finally, dopamine hydrochloride is subjected to end group modification with the dendrimer under the action of a condensing agent, so as to introduce a catechol anchoring group, and after chromatographic purification, a zwitterionic polypeptide dendrimer with both superhydrophilic properties and surface anchoring ability is obtained.
[0022] According to the preferred embodiment of the application, in step A1, the reaction time is 12-14h at 24-26℃.
[0023] According to the preferred embodiment of the application, in step A2, the reaction time is 24-30h at 78-82℃.
[0024] According to the preferred embodiment of the application, in step A3, the reaction time is 4-6h at 3-5℃.
[0025] According to the preferred embodiment of the application, in step A4, the reaction time is 24-30h at 24-26℃.
[0026] Compared with the prior art, the application has the following beneficial effects:
[0027] The multifunctional cardiovascular coating material with superhydrophilic properties provided by the application exhibits significant technical progress and outstanding practical effects, and its comprehensive performance is obviously superior to that of the prior art. First, the coating material realizes excellent superhydrophilic properties and anticoagulant properties, and through unique zwitterionic dendrimer design and accurate surface modification process, a stable hydration layer barrier is formed on the surface of the instrument. This barrier can effectively prevent non-specific protein adsorption and platelet activation, thereby significantly reducing the risk of thrombosis. Experiments prove that the surface of the vascular stent modified by the coating has an extremely low contact angle, can maintain superhydrophilic properties for a long time, and the adsorption amount of various plasma proteins is reduced to an extremely low level, and the number of platelet adhesion is greatly reduced, thereby exhibiting excellent blood compatibility.
[0028] In terms of coating stability and biocompatibility, the application realizes firm combination between the coating and the substrate by optimizing the cross-linking process and molecular structure design. After the simulation blood flow flushing experiment verification, the coating can still maintain the complete structure and function under the long-term implantation condition, and there is no obvious peeling or performance attenuation phenomenon. The mechanical performance and flexibility of the coating reach a good balance, which can adapt to the deformation demand caused by blood vessel pulsation. In the biological evaluation, the coating material shows excellent cell compatibility, has no inhibitory effect on the proliferation of endothelial cells, and has obvious inhibitory effect on the excessive proliferation of smooth muscle cells, which provides favorable conditions for preventing in-stent restenosis. The chemical properties of the coating surface can also adjust the inflammatory response and reduce the degree of foreign body reaction after implantation.
[0029] In addition, the application successfully realizes the organic integration and synergistic effect of multiple biological functions. Based on the antifouling background of zwitterionic chemistry and the functional modification of bioactive molecules, the coating has multiple properties such as anticoagulation, anti-proliferation, antibiosis and promotion of endothelial repair. It is particularly worth noting that the preparation process of the coating has good universality and scalability, which can adapt to the surface modification needs of different geometric shapes of instruments, including difficult to handle areas such as the inner wall of complex structure catheter. The modified compounds used in the coating preparation process are obtained completely through chemical synthesis, avoiding the batch difference problem of biological materials, ensuring the consistency and repeatability of product quality. The technology provides a comprehensive and effective solution to the clinical challenges of thrombosis, intimal hyperplasia and infection faced by cardiovascular implant instruments, and has broad clinical application prospects and important social value. DETAILED DESCRIPTION
[0030] For the purpose of facilitating the understanding of the present application, the present application is illustrated by the following examples. It should be apparent to those skilled in the art that the examples are only for the purpose of understanding the present application and should not be regarded as specific limitations to the present application.
[0031] Some components in the examples and comparative examples are as follows:
[0032] The vascular stent is purchased from Shanghai Minimally Invasive Medical Equipment (Group) Co., Ltd.
[0033] The hydroxyethyl methacrylate is purchased from China Reagent Co., Ltd.
[0034] The acrylamide is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0035] The genipin is purchased from Xi'an Tianyi Biotechnology Co., Ltd.
[0036] The polyethylene glycol-poly (lactic acid) block copolymer is purchased from Jinan Daigang Biotechnology Co., Ltd.
[0037] The 2-hydroxy-2-methylpropiophenone is purchased from Shanghai Titan Science and Technology Co., Ltd.
[0038] The heparin sodium is purchased from Changshan Pharmaceutical Co., Ltd.
[0039] The fourth generation polyamide-amine dendrimer is purchased from Weihai Chen Yuan Molecular New Material Co., Ltd.
[0040] The bromoacetic acid is purchased from National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0041] The N,N'-diisopropyl carbodiimide is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0042] The ethylenediamine is purchased from National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0043] The 2-methyl-2-oxazoline is purchased from Tianjin Xinsisheng Biochemical Technology Co., Ltd.
[0044] The 2-ethyl-2-oxazoline is purchased from Shanghai Bide Pharmaceutical Technology Co., Ltd.
[0045] The methyl p-toluenesulfonate is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0046] The 2-acrylamide-2-methylpropane sulfonic acid is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0047] The 1-ethyl-3-(3-dimethylaminopropyl) carbodiimide hydrochloride is purchased from Shanghai Titan Science and Technology Co., Ltd.
[0048] The N-hydroxysuccinimide is purchased from Shanghai Titan Science and Technology Co., Ltd.
[0049] The dimethylaminoethyl methacrylate is purchased from National Pharmaceutical Group Chemical Reagent Co., Ltd.
[0050] The azobisisobutyronitrile is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0051] The 1,3-propane sultone is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0052] The iodomethane is purchased from Shanghai Bide Pharmaceutical Technology Co., Ltd.
[0053] The dopamine hydrochloride is purchased from Aladdin Reagent (Shanghai) Co., Ltd.
[0054] The N-(3-dimethylaminopropyl)-N'-ethyl carbodiimide hydrochloride is purchased from Shanghai Maikelin Biochemical Technology Co., Ltd.
[0055] Example 1
[0056] The present embodiment provides a method for preparing a multifunctional cardiovascular coating material with superhydrophilicity. Preparation of zwitterionic polypeptide dendrimers: Step Al, 10.0 g of fourth generation polyamide-amine dendrimers were dissolved in 200 mL of anhydrous dimethyl sulfoxide, 8.2 g of bromoacetic acid and 9.2 g of N,N'-diisopropyl carbodiimide were added, and the reaction was carried out at 25 °C for 13 h under nitrogen protection; then the solvent was removed by vacuum distillation to obtain a solid product, which was redissolved in a boric acid buffer with a pH value of 8.5, 4.8 g of ethylenediamine was added, and the reaction was carried out at 4 °C for 24 h, and finally purified by dialysis to obtain activated dendrimers. Step A2, 10.0 g of 2-methyl-2-oxazoline and 8.0 g of 2-ethyl-2-oxazoline were dissolved in 120 mL of acetonitrile, 1.5 g of methyl p-toluenesulfonate was added, and the reaction was carried out at 80 °C for 27 h under refluxing and nitrogen protection to obtain a linear polyoxazoline intermediate; the reaction system was cooled to 45 °C, 100 mL of a methanol solution containing 0.8% sodium methoxide was added, and the reaction was carried out at 63 °C for 5 h; then 15.0 g of 2-acrylamide-2-methylpropanesulfonic acid, 3.2 g of 1-ethyl-3-dimethylaminopropyl carbodiimide hydrochloride, and 1.9 g of N-hydroxysuccinimide were added, and the reaction was carried out at 28 °C for 14 h; finally, the sulfonic acid functionalized polyoxazoline side chain was obtained by purification through cold ethanol precipitation. Step A3, 5.0 g of activated dendrimers prepared in Step Al were dissolved in a 2-morpholinoethanesulfonic acid buffer with a pH value of 6.5, 12.0 g of sulfonic acid functionalized polyoxazoline side chains prepared in Step A2 were added, and the reaction was carried out at 4 °C for 5 h, and then the temperature was increased to 25 °C for further reaction for 19 h; after the reaction was completed, the dendrimer-polyoxazoline conjugate was obtained by ultrafiltration purification; 8.0 g of the dendrimer-polyoxazoline conjugate was dissolved in a carbonate buffer with a pH value of 9.0, 12.0 g of dimethylaminoethyl methacrylate and 0.5 g of azobisisobutyronitrile were added, and the reaction was carried out at 73 °C for 3 h to introduce tertiary amine groups; then 4.2 g of 1,3-propanesultone and 3.8 g of iodomethane were added in sequence, and the reaction was carried out at 45 °C for 28 h to form a zwitterionic structure. Step A4, 8.0 g of the zwitterionic dendrimer-polyoxazoline conjugate prepared in Step A3 was dissolved in a sodium acetate buffer with a pH value of 5.0 together with 2.8 g of dopamine hydrochloride, 2.1 g of N-3-dimethylaminopropyl-N'-ethyl carbodiimide hydrochloride and 1.3 g of N-hydroxysuccinimide were added, and the reaction was carried out at 25 °C for 28 h under light protection and nitrogen protection to obtain a reaction mixture; the reaction mixture was purified by size exclusion chromatography and ion exchange chromatography, and finally freeze-dried to obtain zwitterionic polypeptide dendrimers.
[0057] Preparation of multifunctional cardiovascular coating material with superhydrophilicity: Step S1, a cardiovascular stent was sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min; the cleaned device was immersed in a mixed solution of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, and treated at 60°C for 45 min to obtain a heat-treated cardiovascular stent; the heat-treated cardiovascular stent was transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane in toluene solution, and reacted at 65°C for 6 h under nitrogen protection; finally, it was washed with deionized water and dried with nitrogen to obtain an aminated cardiovascular stent surface. Step S2, 20.0 g of hydroxyethyl methacrylate, 10.0 g of acrylamide and 5.0 g of zwitterionic polypeptide dendrimer were dissolved in 100 mL of phosphate buffer solution with a pH value of 7.4 to form a solution, 2.0 g of genipin, 4.0 g of polyethylene glycol-poly lactic acid block copolymer and 0.5 g of 2-hydroxy-2-methyl propiophenone were added, and the mixture was stirred in the dark for 5 h to obtain a coating solution, which was coated on the aminated cardiovascular stent surface to obtain a coated cardiovascular stent. Step S3, the coated cardiovascular stent was placed in a UV crosslinking instrument under nitrogen protection, and irradiated under 365 nm ultraviolet light with an intensity of 15 mW / cm² for 120 s; it was then transferred to a constant temperature and humidity chamber and kept at 25°C for 13 h; then it was immersed in 37°C physiological saline for 48 h to obtain a crosslinked cardiovascular stent coating. Step S4, the crosslinked cardiovascular stent coating was immersed in a 1 mg / mL heparin sodium solution and soaked at 4°C for 28 h to obtain a functionalized coating; the functionalized coating was washed with sterile deionized water, dried in a vacuum drying oven, and finally sterilized by low temperature plasma treatment at a power of 200 W for 30 min.
[0058] Example 2
[0059] The difference between this example and Example 1 is in the preparation of the zwitterionic polypeptide dendrimer: Step Al, 10.0 g of the fourth generation polyamidoamine dendrimers were dissolved in 200 mL of anhydrous dimethyl sulfoxide, 7.5 g of bromoacetic acid and 8.5 g of N,N'-diisopropylcarbodiimide were added, and the reaction was carried out at 24 °C for 12 h under nitrogen protection; then the solvent was removed by distillation under reduced pressure to obtain a solid product, which was redissolved in a boric acid buffer with a pH value of 8.4, 4.5 g of ethylenediamine was added, and the reaction was carried out at 3 °C for 26 h, and finally purified by dialysis to obtain the activated dendrimers. Step A2, 9.0 g of 2-methyl-2-oxazoline and 7.0 g of 2-ethyl-2-oxazoline were dissolved in 100 mL of acetonitrile, 1.3 g of methyl p-toluenesulfonate was added, and the reaction was carried out at 78 °C under reflux for 24 h to obtain a linear polyoxazoline intermediate; the reaction system was cooled to 40 °C, 90 mL of a methanol solution containing 0.5% sodium methoxide was added, and the reaction was carried out at 60 °C for 6 h; then 12.0 g of 2-acrylamide-2-methylpropanesulfonic acid, 3.0 g of 1-ethyl-3-dimethylaminopropyl carbodiimide hydrochloride and 1.7 g of N-hydroxysuccinimide were added, and the reaction was carried out at 25 °C for 12 h; finally, purification by cold ethanol precipitation was performed to obtain sulfonic acid group functionalized polyoxazoline side chains. Step A3, 5.0 g of the activated dendrimers prepared in Step Al were dissolved in a 2-morpholinoethanesulfonic acid buffer with a pH value of 6.4, 10.0 g of the sulfonic acid group functionalized polyoxazoline side chains prepared in Step A2 were added, and the reaction was carried out at 3 °C for 4 h, and then the temperature was increased to 24 °C for continued reaction for 18 h; after the reaction was completed, purification by ultrafiltration was performed to obtain dendrimer-polyoxazoline conjugates; 8.0 g of the dendrimer-polyoxazoline conjugates were dissolved in a carbonate buffer with a pH value of 8.8, 10.0 g of dimethylaminoethyl methacrylate and 0.4 g of azobisisobutyronitrile were added, and the reaction was carried out at 70 °C for 4 h to introduce tertiary amine groups; then 3.8 g of 1,3-propanesultone and 3.5 g of iodomethane were added in sequence, and stirring was carried out at 44 °C for 24 h to form a zwitterionic structure. Step A4, 8.0 g of the zwitterionic dendrimer-polyoxazoline conjugates prepared in Step A3 were dissolved in a sodium acetate buffer with a pH value of 4.8 together with 2.5 g of dopamine hydrochloride, 2.0 g of N-3-dimethylaminopropyl-N'-ethylcarbodiimide hydrochloride and 1.2 g of N-hydroxysuccinimide were added, and the reaction was carried out at 24 °C for 24 h under light shielding and nitrogen protection to obtain a reaction mixture; the reaction mixture was purified by size exclusion chromatography and ion exchange chromatography, and finally freeze-dried to obtain the zwitterionic polypeptide dendrimer.
[0060] Preparation of multifunctional cardiovascular coating material with superhydrophilicity: Step S1, a cardiovascular stent was sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min; the cleaned device was immersed in a mixed solution of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, and treated at 58°C for 60 min to obtain a heat-treated cardiovascular stent; the heat-treated cardiovascular stent was transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane in toluene solution, and reacted at 64°C for 7 h under nitrogen protection; finally, it was washed with deionized water, dried with nitrogen, and the aminated cardiovascular stent surface was obtained. Step S2, 18.0 g of hydroxyethyl methacrylate, 9.0 g of acrylamide and 4.0 g of zwitterionic polypeptide dendrimer were dissolved in 100 mL of phosphate buffer solution with a pH value of 7.2 to form a solution, 1.8 g of genipin, 3.5 g of polyethylene glycol-poly lactic acid block copolymer and 0.4 g of 2-hydroxy-2-methyl propiophenone were added, and the mixture was stirred in the dark for 4 h to obtain a coating solution, which was coated on the aminated cardiovascular stent surface to obtain a coated cardiovascular stent. Step S3, the coated cardiovascular stent was placed in a UV crosslinking instrument under nitrogen protection, and irradiated under 365 nm ultraviolet light with an intensity of 15 mW / cm² for 110 s; it was transferred to a constant temperature and humidity box and kept at 24°C for 12 h; then it was immersed in 36°C physiological saline for 50 h to obtain a crosslinked cardiovascular stent coating. Step S4, the crosslinked cardiovascular stent coating was immersed in a 1 mg / mL heparin sodium solution and soaked at 2°C for 30 h to obtain a functionalized coating; the functionalized coating was washed with sterile deionized water, dried in a vacuum drying oven, and finally sterilized by low temperature plasma treatment at a power of 200 W for 25 min.
[0061] Example 3
[0062] The difference between this example and Example 1 is in the preparation of the zwitterionic polypeptide dendrimer: Step Al, 10.0 g of the fourth generation polyamidoamine dendrimers were dissolved in 200 mL of anhydrous dimethyl sulfoxide, 8.8 g of bromoacetic acid and 9.8 g of N,N'-diisopropylcarbodiimide were added, and the reaction was carried out at 26 °C for 14 h under nitrogen protection; then the solvent was removed by distillation under reduced pressure to obtain a solid product, which was redissolved in a boric acid buffer with a pH value of 8.6, 5.2 g of ethylenediamine was added, and the reaction was carried out at 5 °C for 22 h, and finally purified by dialysis to obtain the activated dendrimers. Step A2, 11.0 g of 2-methyl-2-oxazoline and 9.0 g of 2-ethyl-2-oxazoline were dissolved in 150 mL of acetonitrile, 1.7 g of methyl p-toluenesulfonate was added, and the reaction was carried out at 82 °C for 30 h under refluxing and nitrogen protection to obtain a linear polyoxazoline intermediate; the reaction system was cooled to 50 °C, 120 mL of a methanol solution containing 1.0% sodium methoxide was added, and the reaction was carried out at 65 °C for 4 h; then 18.0 g of 2-acrylamide-2-methylpropanesulfonic acid, 3.5 g of 1-ethyl-3-dimethylaminopropyl carbodiimide hydrochloride and 2.1 g of N-hydroxysuccinimide were added, and the reaction was carried out at 30 °C for 16 h; finally, the sulfonic acid group functionalized polyoxazoline side chain was obtained by purification through cold ethanol precipitation. Step A3, 5.0 g of the activated dendrimers prepared in Step Al were dissolved in a 2-morpholinoethanesulfonic acid buffer with a pH value of 6.6, 15.0 g of the sulfonic acid group functionalized polyoxazoline side chain prepared in Step A2 was added, and the reaction was carried out at 5 °C for 6 h, and then the temperature was increased to 26 °C and the reaction was continued for 20 h; after the reaction was completed, the dendrimer-polyoxazoline conjugate was obtained by purification through ultrafiltration; 8.0 g of the dendrimer-polyoxazoline conjugate was dissolved in a carbonate buffer with a pH value of 9.2, 15.0 g of dimethylaminoethyl methacrylate and 0.6 g of azobisisobutyronitrile were added, and the reaction was carried out at 75 °C for 2 h to introduce tertiary amine groups; then 4.5 g of 1,3-propanesultone and 4.2 g of iodomethane were added in sequence, and the reaction was stirred at 46 °C for 30 h to form a zwitterionic structure. Step A4, 8.0 g of the zwitterionic dendrimer-polyoxazoline conjugate prepared in Step A3 was dissolved in a sodium acetate buffer with a pH value of 5.2 together with 3.0 g of dopamine hydrochloride, 2.3 g of N-3-dimethylaminopropyl-N'-ethylcarbodiimide hydrochloride and 1.5 g of N-hydroxysuccinimide were added, and the reaction was carried out at 26 °C for 30 h under light protection and nitrogen protection to obtain a reaction mixture; the reaction mixture was purified by size exclusion chromatography and ion exchange chromatography, and finally the zwitterionic polypeptide dendrimer was obtained by freeze-drying.
[0063] Preparation of multifunctional cardiovascular coating material with superhydrophilicity: Step S1, a cardiovascular stent was sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min; the cleaned device was immersed in a mixed solution of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, and treated at 62°C for 30 min to obtain a heat-treated cardiovascular stent; the heat-treated cardiovascular stent was transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane in toluene solution, and reacted at 66°C for 5h under nitrogen protection; finally, it was washed with deionized water, dried with nitrogen, and the aminated cardiovascular stent surface was obtained. Step S2, 22.0 g of hydroxyethyl methacrylate, 12.0 g of acrylamide and 6.0 g of zwitterionic polypeptide dendrimer were dissolved in 100 mL of phosphate buffer solution with a pH value of 7.6 to form a solution, 2.2 g of gossypol, 4.5 g of polyethylene glycol-poly lactic acid block copolymer and 0.6 g of 2-hydroxy-2-methyl propiophenone were added, and the mixture was stirred in the dark for 6h to obtain a coating solution, which was coated on the aminated cardiovascular stent surface to obtain a coated cardiovascular stent. Step S3, the coated cardiovascular stent was placed in a UV crosslinking instrument under nitrogen protection, and irradiated under 365 nm ultraviolet light with an intensity of 15 mW / cm² for 130 s; it was transferred to a constant temperature and humidity box and kept at 26°C for 14h; then it was immersed in 38°C physiological saline for 46h to obtain a crosslinked cardiovascular stent coating. Step S4, the crosslinked cardiovascular stent coating was immersed in a 1 mg / mL heparin sodium solution and soaked at 6°C for 24h to obtain a functionalized coating; the functionalized coating was washed with sterile deionized water, dried in a vacuum drying oven, and finally sterilized by low temperature plasma treatment at a power of 200W for 35 min.
[0064] Comparative Example 1
[0065] The difference between the present comparative example and Example 1 is that no zwitterionic polypeptide dendrimer is added in the coating preparation. Step S1, the vascular stent is sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min each; the cleaned device is immersed in a mixture of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, treated at 60°C for 45 min to obtain a heat-treated vascular stent; the heat-treated vascular stent is transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane toluene solution, reacted at 65°C for 6h under nitrogen protection; finally washed with deionized water and dried with nitrogen to obtain an aminated vascular stent surface. Step S2, 20.0g of hydroxyethyl methacrylate and 10.0g of acrylamide are dissolved in 100mL of phosphate buffer solution with a pH value of 7.4 to form a solution, 2.0g of genipin, 4.0g of polyethylene glycol-poly lactic acid block copolymer and 0.5g of 2-hydroxy-2-methylpropiophenone are added, and stirred for 5h under light-proof conditions to obtain a coating solution, which is coated on the aminated vascular stent surface to obtain a coated vascular stent. The subsequent steps S3 and S4 are exactly the same as those in Example 1.
[0066] Comparative Example 2
[0067] The difference between the present comparative example and Example 1 is that no zwitterionic polypeptide dendrimer is added in the coating preparation. Step S1, the vascular stent is sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min each; the cleaned device is immersed in a mixture of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, treated at 60°C for 45 min to obtain a heat-treated vascular stent; the heat-treated vascular stent is transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane toluene solution, reacted at 65°C for 6h under nitrogen protection; finally washed with deionized water and dried with nitrogen to obtain an aminated vascular stent surface. Step S2, 20.0g of hydroxyethyl methacrylate and 10.0g of acrylamide are dissolved in 100mL of phosphate buffer solution with a pH value of 7.4 to form a solution, 2.0g of genipin, 4.0g of polyethylene glycol-poly lactic acid block copolymer and 0.5g of 2-hydroxy-2-methylpropiophenone are added, and stirred for 5h under light-proof conditions to obtain a coating solution, which is coated on the aminated vascular stent surface to obtain a coated vascular stent. The subsequent steps S3 and S4 are exactly the same as those in Example 1.
[0068] Comparative Example 3
[0069] The difference between the present comparative example and Example 1 is that a non-zwitterionic dendritic polymer is used instead of the zwitterionic polypeptide dendrimer in the coating preparation. Step S1, the vascular stent is sequentially immersed in acetone, ethanol and deionized water for ultrasonic cleaning for 15 min; the cleaned device is immersed in a mixture of concentrated sulfuric acid and 30% hydrogen peroxide with a volume ratio of 3:1, treated at 60°C for 45 min to obtain a heat-treated vascular stent; the heat-treated vascular stent is transferred into a 2% volume fraction of 3-aminopropyl triethoxysilane in toluene solution, reacted at 65°C for 6 h under nitrogen protection; finally washed with deionized water and dried with nitrogen to obtain an aminated vascular stent surface. Step S2, 20.0 g of hydroxyethyl methacrylate, 10.0 g of acrylamide and 5.0 g of dendritic polymer only activated by step A1 are dissolved in 100 mL of phosphate buffer solution with a pH value of 7.4 to form a solution, 2.0 g of genipin, 4.0 g of polyethylene glycol-poly lactic acid block copolymer and 0.5 g of 2-hydroxy-2-methyl propiophenone are added, stirred in the dark for 5 h to obtain a coating solution, and the coating solution is coated on the aminated vascular stent surface to obtain a coated vascular stent. The subsequent steps S3 and S4 are exactly the same as Example 1.
[0070] The performance of the multifunctional cardiovascular coating material with superhydrophilicity provided in the above examples and comparative examples is tested according to the test specifications of national and industry standards, and the test methods are as follows: the superhydrophilicity of the coating is measured by a contact angle measuring instrument at 25°C, using ultrapure water as the test liquid, measuring the contact angle at 5 different positions on the coating surface and taking the average value; the protein adsorption resistance is tested by a quartz crystal microbalance, after the coating sample is equilibrated in a phosphate buffer solution with a pH value of 7.4, 1 mg / mL fibrinogen solution is injected, the frequency change is monitored to calculate the protein adsorption amount; the anticoagulant property is tested by a platelet adhesion experiment, 200 μL of fresh platelet-rich plasma is incubated with the coating sample at 37°C for 1 h, after being fixed by 2.5% glutaraldehyde and dehydrated by gradient ethanol, the platelet adhesion amount is observed and counted by scanning electron microscopy; the hemocompatibility is evaluated by a hemolysis rate experiment, the coating sample is incubated with 0.2 mL of anticoagulant whole blood at 37°C for 1 h, after centrifugation, the absorbance at 540 nm of the supernatant is measured; the coating stability is tested by continuously flushing the sample in a phosphate buffer solution with a flow rate of 1.5 m / s for 7 d, and the weight loss and contact angle change are detected regularly; the biocompatibility is measured by a CCK-8 method to determine the relative proliferation rate of cells, the coating extract is co-cultured with L929 cells for 24 h; the antibacterial property is evaluated by a colony counting method, 10 6 CFU / mL bacterial suspension is co-cultured with the coating sample for 24 h to calculate the bacterial adhesion rate.
[0071] The performance test data are shown in Table 1.
[0072] Table 1 Performance test results
[0073] Test item Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 Water contact angle (°) 8.2 9.1 8.7 72.5 65.3 58.6 Fibrinogen adsorption amount (ng / cm2) 7.5 8.9 8.1 285.6 192.4 125.3 Platelet adhesion amount (cells / mm2) 312 385 356 17560 12450 8560 Hemolysis rate (%) 0.12 0.18 0.15 3.25 2.41 1.68 Weight loss rate (%) after 7 days of flushing 2.1 2.8 2.4 35.6 28.4 15.2 Cell relative proliferation rate (%) 98.3 96.7 97.5 85.2 88.6 91.3 Staphylococcus aureus adhesion rate (%) 4.2 5.1 4.7 86.5 78.3 65.2 Escherichia coli adhesion rate (%) 3.8 4.6 4.2 82.7 75.6 60.8
[0074] From the above, embodiments 1-3 effectively solve the key technical problems that the present application aims to overcome compared to comparative examples 1-3. The coating material prepared in embodiments 1-3 achieves significant superhydrophilicity, with a water contact angle of less than 10°, while the contact angles of comparative examples 1-3 are all higher than 58°, proving that the introduction of zwitterionic polypeptide dendrimers successfully builds a stable hydration layer, solving the problem of insufficient hydrophilicity of traditional coatings. In terms of anti-biofouling, the fibrinogen adsorption of the embodiments is less than 9 ng / cm², and the number of platelet adhesion is not more than 385 cells / mm², which is much lower than 285.6 ng / cm² and 17560 cells / mm² of comparative example 1, indicating that the coating can effectively resist protein non-specific adsorption and platelet activation, solving the risk of thrombosis of implanted devices. Blood compatibility tests show that the hemolysis rate of embodiments is less than 0.2%, while that of comparative examples is more than 1.6%, proving that the material has good blood compatibility. In terms of coating stability, the weight loss rate of embodiments after 7 days of flushing is not more than 2.8%, while that of comparative example 1 is as high as 35.6%, indicating that through molecular structure design and cross-linking process optimization, the technical problem of easy peeling of the coating in body fluid environment is effectively solved. The relative proliferation rate of cells in the biocompatibility evaluation of embodiments is higher than 96%, which is significantly better than 85.2-91.3% of comparative examples, indicating that the material has no cytotoxicity. The anti-bacterial performance test shows that the adhesion rate of embodiments to two common pathogenic bacteria is less than 5.1%, while that of comparative examples is more than 60%, proving that the coating has broad-spectrum anti-biofouling ability. It is particularly noteworthy that the performance of comparative example 2 decreases significantly after using ordinary polyacrylamide instead of modified compounds, indicating that pure hydrophilic segments cannot achieve the synergistic anti-pollution effect of zwitterionic structure; the use of incompletely functionalized dendritic polymers in comparative example 3 also leads to performance degradation, proving that the complete zwitterionic structure is crucial to achieving superhydrophilicity and anticoagulant function. In summary, embodiments 1-3 successfully solve the multiple clinical challenges of coagulation, infection and intimal hyperplasia faced by cardiovascular implant devices through innovative zwitterionic polypeptide dendrimer design, achieving the perfect unity of superhydrophilicity and multifunctionality.
Claims
1. A method for preparing a multifunctional cardiovascular coating material with superhydrophilic properties, characterized in that, Includes the following steps: S1. The vascular stent is sequentially immersed in acetone, ethanol, and deionized water for ultrasonic cleaning. After cleaning, the stent is immersed in a mixture of concentrated sulfuric acid and hydrogen peroxide and treated at 58-62°C to obtain a heat-treated vascular stent. The heat-treated vascular stent is then transferred to a toluene solution of 3-aminopropyltriethoxysilane and reacted at 64-66°C under nitrogen protection. Finally, the stent is rinsed with deionized water and dried with nitrogen to obtain an amination-treated vascular stent surface. S2. Hydroxyethyl methacrylate, acrylamide, and zwitterionic peptide dendritic macromolecules are dissolved in phosphate buffer solution at pH 7.2-7.6 to form a solution. Genipin, polyethylene glycol-polylactic acid block copolymer, and 2-hydroxy-2-methylphenylacetone are added. The solution is stirred under light-protected conditions to obtain a coating solution. The coating solution is then coated onto the surface of the aminated vascular stent to obtain the coated vascular stent. S3. Place the coated vascular stent in a UV crosslinker under nitrogen protection and irradiate it with UV light; transfer it to a constant temperature and humidity chamber and maintain it at 24-26℃; then immerse it in physiological saline at 36-38℃ to obtain the crosslinked vascular stent coating. S4. Immerse the cross-linked vascular stent coating in heparin sodium solution at 2-6℃ to obtain the functionalized coating; rinse the functionalized coating with sterile deionized water, dry it in a vacuum drying oven, and finally sterilize it with low-temperature plasma.
2. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 1, characterized in that, In step S1, the treatment time is 30-60 minutes at 58-62℃.
3. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 1, characterized in that, In step S2, the stirring time under light-protected conditions is 4-6 hours.
4. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 1, characterized in that, In step S3, maintain the temperature at 24-26℃ for 12-14 hours.
5. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 1, characterized in that, In step S4, the soaking time at 2-6℃ is 24-30 hours.
6. The method for preparing a multifunctional cardiovascular coating material with superhydrophilic properties according to any one of claims 1-5, characterized in that, The preparation steps of the zwitterionic peptide dendritic macromolecule include: A1. The fourth-generation polyamide-amine dendritic polymer was dissolved in anhydrous dimethyl sulfoxide, and bromoacetic acid and N,N'-diisopropylcarbodiimide were added. The reaction was carried out at 24-26℃ under nitrogen protection. Subsequently, the solid product was obtained by vacuum distillation. The solid product was redissolved in borate buffer solution with pH=8.4-8.6, and ethylenediamine was added. The reaction was carried out at 3-5℃. Finally, the activated dendritic polymer was obtained by dialysis purification. A2. 2-Methyl-2-oxazoline and 2-ethyl-2-oxazoline were dissolved in acetonitrile, and methyl p-toluenesulfonate was added. The mixture was refluxed at 78-82°C under nitrogen protection to obtain a linear polyoxazoline intermediate. The mixture was cooled to 40-50°C, and a methanol solution containing sodium methoxide was added. The mixture was reacted at 60-65°C. Subsequently, 2-acrylamido-2-methylpropanesulfonic acid, 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide hydrochloride, and N-hydroxysuccinimide were added. The mixture was reacted at 25-30°C. Finally, the mixture was purified by cold ethanol precipitation to obtain sulfonic acid-functionalized polyoxazoline side chains. A3. Dissolve the activated dendritic polymer prepared in step A1 in 2-morpholine ethanesulfonic acid buffer at pH 6.4-6.6, add the sulfonic acid-functionalized polyoxazoline side chain prepared in step A2, react at 3-5℃, and then raise the temperature to 24-26℃ to continue the reaction; after the reaction is completed, purify by ultrafiltration to obtain the dendritic-polyoxazoline conjugate; dissolve the dendritic-polyoxazoline conjugate in carbonate buffer at pH 8.8-9.2, add dimethylaminoethyl methacrylate and azobisisobutyronitrile, react at 70-75℃ to introduce tertiary amine groups; then add 1,3-propanesulfonic acid lactone and iodomethane in sequence, stir at 44-46℃ to form a zwitterionic structure; A4. The zwitterionic dendritic-polyoxazoline conjugate prepared in step A3 was dissolved together with dopamine hydrochloride in sodium acetate buffer at pH 4.8-5.
2. N-(3-dimethylaminopropyl)-N'-ethylcarbodiimide hydrochloride and N-hydroxysuccinimide were added. The mixture was reacted at 24-26°C under light-protected conditions and nitrogen protection to obtain the reaction mixture. The reaction mixture was purified by size exclusion chromatography and ion exchange chromatography, and finally lyophilized.
7. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 6, characterized in that, In step A1, the reaction time is 12-14 hours at 24-26℃.
8. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 6, characterized in that, In step A2, the reflux reaction at 78-82℃ takes 24-30 hours.
9. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 6, characterized in that, In step A3, the reaction time is 4-6 hours at 3-5℃.
10. The method for preparing the multifunctional cardiovascular coating material with superhydrophilic properties according to claim 6, characterized in that, In step A4, the reaction is carried out at 24-26℃ for 24-30 hours.
Citation Information
Patent Citations
Synthesis method for amphoteric ion copolymer for well drilling fluid
CN104926986A
Polymer, composition and coating and product thereof
CN113698535A
Organic-inorganic hybrid polymer based fluids
US20160177163A1
Hydrate inhibitor carrying hydrogel
US20180265647A1
Zwitterionic biocompatible polymers, methods, and uses thereof
US20210228737A1